Comparison of the Efficiency of Dendritic Cell Maturation Upon Stimulation with Bacterial Lipopolysaccharide or Tumor Necrosis Factor Alfa - Titov, E.A.; Plisova, V.K.; Pokusaeva, I.A.; Saryglar, R.Yu.; Kholodenko, I.V.; Bystrykh, O.A.; Kuprin, A.V.; Yarygin, K.N.; Lupatov, A.Yu. (Biomedical Chemistry: Research and Methods, 2025)
Dendritic cells (DCs) are the professional antigen-presenting cells capable of presenting antigens to T-lymphocytes, thereby initiating the primary immune response. The unique immunological properties of this cell population make their use as a cellular vaccine relevant for the treatment of oncological and chronic infectious diseases. A critical stage in obtaining DCs with immunostimulatory properties is their maturation. To compare the effectiveness of alternative methods for stimulating maturation, DCs were obtained in vitro from peripheral blood monocytes through their induced differentiation in the presence of the cytokines GM-CSF and IL-4. As biochemical stimuli for inducing maturation, bacterial lipopolysaccharide (LPS) or tumor necrosis factor alpha combined with prostaglandin E2 (TNFα+PGE2) were used. No significant differences were found in the ability of these factors to stimulate the expression of HLA-DR and costimulatory molecules (CD80, CD83, CD86). The use of alternative maturations did not lead to differences in the ability of DCs to stimulate the proliferation of allogeneic lymphocytes. At the same time, there were morphological signs indicating the ability of LPS to stimulate differentiation into macrophages.